1998
DOI: 10.1002/(sici)1097-0274(199812)34:6<623::aid-ajim11>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to green coffee beans and work-related allergic symptoms in coffee workers

Abstract: Background Occupational respiratory allergy to green coffee beans (GCB) and to castor beans (CB) was studied in 112 workers in a modern coffee manufacturing plant of Trieste (Italy), where the process is completely automatic, the environmental conditions are good and where exposure to CB can be considered absent because since 1970, only new sacks have been used for coffee transportation. Methods All subjects were interviewed by a trained doctor using a questionnaire to investigate allergic symptoms and predisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 6 publications
(11 reference statements)
2
15
0
1
Order By: Relevance
“…The dust from primary coffee processing has been reported to contain a higher percent of larger, coarse particles from the husks (Smith et al, 1985), which may be different from the dust in secondary processing. However, the range of total dust levels in secondary coffee factories is reported to be comparable to our study (0.07–63mg/m 3 ; Zuskin et al, 1979; Jones et al, 1982; Thomas et al, 1991; Larese et al, 1998). …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The dust from primary coffee processing has been reported to contain a higher percent of larger, coarse particles from the husks (Smith et al, 1985), which may be different from the dust in secondary processing. However, the range of total dust levels in secondary coffee factories is reported to be comparable to our study (0.07–63mg/m 3 ; Zuskin et al, 1979; Jones et al, 1982; Thomas et al, 1991; Larese et al, 1998). …”
Section: Discussionsupporting
confidence: 87%
“…Mean values for total dust were not given in those studies; hence, we cannot compare further. Other exposure studies in the coffee industry have been performed in secondary factories in Croatia, the USA, United Kingdom, Italy, and Germany (Zuskin et al, 1979; Jones et al, 1982; Thomas et al, 1991; Larese et al, 1998; Oldenburg et al, 2009), where the difference in the dust content might be due to the different stage in coffee processing. The dust from primary coffee processing has been reported to contain a higher percent of larger, coarse particles from the husks (Smith et al, 1985), which may be different from the dust in secondary processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to know if the reported symptoms may develop into more serious conditions. Previous studies have shown that work with green coffee may cause both irritation and allergic respiratory symptoms [4,7]: Some studies suggest that coffee workers may develop allergic alveolitis [24] while others suggest asthma [10,22]. …”
Section: Discussionmentioning
confidence: 99%
“…In Croatia, a study done among healthy individuals showed that exposure to coffee dust extracts induced a significant decrease in lung function and increased bronchial hyperresponsiveness [12]. Workers in secondary coffee processing (in coffee silos, coffee haulage companies, and coffee manufacturing companies) had reduced lung function and higher prevalence of chronic cough and chronic bronchitis than controls [4,7,8,12]. The few studies [1,9,13] done in developing countries where primary coffee processing (curing) takes place, also indicated that exposed workers have an increased risk of developing airway symptoms.…”
Section: Introductionmentioning
confidence: 99%